2013
DOI: 10.1590/s1809-98232013000400014
|View full text |Cite
|
Sign up to set email alerts
|

Força muscular e qualidade de vida em idosas

Abstract: OBJETIVO: Verificar o efeito do treinamento físico sobre os níveis de força e a qualidade de vida, considerando capacidade funcional, limitações físicas, dor, estado geral de saúde, vitalidade e variáveis de relação social em idosas institucionalizadas. MÉTODOS: Participaram do estudo 36 idosas com 60 ou mais anos de idade, recrutadas no Serviço Social do Comércio (SESC), na cidade de São Luís-MA, compondo dois grupos: sedentário (n=16) e treinamento (n=20). Determinou-se a força muscular isométrica máxima dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
6
0
16
Order By: Relevance
“…Mokhtari et al (2012) reported that Pilates exercises decreased depression by increasing blood serotonin level. Researchers informed that physical exercise such as strength training, combine exercises, tai chi as well as Pilates exercise is an effective non-pharmacological intervention to improve cognitive performance and quality of life in elderly (Tavares et al,2014;Mariano et al,2013;de Carvalho Bastone).…”
Section: Discussionmentioning
confidence: 99%
“…Mokhtari et al (2012) reported that Pilates exercises decreased depression by increasing blood serotonin level. Researchers informed that physical exercise such as strength training, combine exercises, tai chi as well as Pilates exercise is an effective non-pharmacological intervention to improve cognitive performance and quality of life in elderly (Tavares et al,2014;Mariano et al,2013;de Carvalho Bastone).…”
Section: Discussionmentioning
confidence: 99%
“…No que se refere às características funcionais, pesquisas anteriores mostraram que os indivíduos com melhor desempenho nos testes funcionais apresentam melhor QV, 18,19 assim como os achados da presente pesquisa. Esses resultados não se limitam a de estudos observacionais, como o presente trabalho e o de Gadelha et al 19 , conforme demonstraram Mariano et al 20 , os quais obtiveram melhoria da QV nos domínios capacidade funcional, estado geral de saúde, vitalidade e saúde mental, após treinamento que levou a ganho significativo de força.…”
Section: Discussionunclassified
“…Although the literature suggests that dynapenia may have a negative impact on health and quality of life, little is known about the repercussions of this condition in patients with HIV. Mariano et al 27 identified a negative correlation between the diagnosis of handgrip strength decrease and quality of life according to two classification criteria and the SF-36 domains.…”
Section: Discussionmentioning
confidence: 99%